An anatomy of gentrification processes: variegating causes of neighbourhood change. (July 2015) - Hochstenbach, Cody; van Gent, Wouter PC
Several theoretical debates in gentrification literature deal with the role and importance of migration, in situ social mobility, and demographic change in urban social change. These debates focus primarily on structural processes. However, we have comparatively little insight into how and to what degree different mechanisms actually underpin upgrading in urban neighbourhoods. This paper uses Dutch register data to show how residential mobility, social mobility, and demographic change each contribute to gentrification in Amsterdam and Rotterdam. First, our findings show that residential mobility remains key to understanding the growth of higher-income residents in gentrifiying neighbourhoods. At the same time, social mobility and demographic change— notably ageing—are most important in explaining dwindling numbers of lower-income residents. Second, large differences exist across neighbourhoods. By mapping three idealtypical drivers of gentrification, we show how the migration-based 'displacement model' occurs predominantly in upgrading neighbourhoods with a high status. Conversely, in low-status upgrading neighbourhoods social mobility is more important in explaining gentrification. These different forms of upgrading occur simultaneously in both cities and should be integrated to advance our understanding of gentrification as a process that is both widespread and occurs in different, ever-changing forms across neighbourhoods.